Is the lady's-slipper orchid (Cypripedium calceolus) likely to shortly become extinct in Europe?-Insights based on ecological niche modelling - Kolanowska, Marta; Jakubska-Busse, Anna (PloS one, 2020)
Lady's-slipper orchid (Cypripedium calceolus) is considered an endangered species in most countries within its geographical range. The main reason for the decline in the number of populations of this species in Europe is habitat destruction. In this paper the ecological niche modelling approach was used to estimate the effect of future climate change on the area of niches suitable for C. calceolus. Predictions of the extent of the potential range of this species in 2070 were made using climate projections obtained from the Community Climate System Model for four representative concentration pathways: rcp2.6, rcp4.5, rcp6.0 and rcp8.5. According to these analyses all the scenarios of future climate change will result in the total area of niches suitable for C. calceolus decreasing. Considering areas characterized by a suitability of at least 0.4 the loss of habitat will vary between ca. 30% and 63%. The highest habitat loss of ca. 63% is predicted to occur in scenario rcp 8.5. Surprisingly, in the most damaging rcp 8.5 prediction the highest overlap between potential range of C. calceolus and its pollinators will be observed and in all other scenarios some pollinators will be available for this species in various geographical regions. Based on these results at least two approaches should be implemented to improve the chances of survival of C. calceolus. In view of the unavoidable loss of suitable habitats in numerous European regions, conservation activities should be intensified in areas where this species will still have suitable niches in the next 50 years. In addition, for C. calceolus ex-situ activities should be greatly increased so that it can be re-introduced in the remaining suitable areas.
Keywords: klimatické změny; Ecosystem; ohrožené druhy; Climate Change; Europe; Endangered Species; Models, Biological; biologické modely; ekosystém; Orchidaceae; Evropa